Climate change impacts on cocoa in Ghana: Results of a Random Forest suitability classification study - Bunn, Christian; Lundy, Mark M.; Castro, Fabio (2016)
The presentation and discussion focused on providing updated climate change projections based on joint work by CIAT and CRIG incorporating climate datasets, current cocoa production sites and soil information.